1987
DOI: 10.1128/aac.31.12.2005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fluconazole and amphotericin B in treating histoplasmosis in immunosuppressed mice

Abstract: Fluconazole (UK-49,858) was compared with amphotericin B in treating histoplasmosis in female AKR mice immunosuppressed with either cyclophosphamide or cortisone. Both drugs protected animals from a lethal challenge with Histoplasma capsulatum, but neither regimen resulted in cures since viable organisms were cultured from spleens of survivors.We have previously shown that the triazole fluconazole 858) given orally was as effective as amphotericin B given by intraperitoneal (i.p.) injection in treating normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

1989
1989
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 12 publications
0
17
1
Order By: Relevance
“…The relative failure of oral agents like itraconazole and fluconazole was somewhat surprising, because they have been reported to be effective in the therapy of experimental fungal infections in mice (5,11,25). In the current study, the model infections were designed to present a formidable challenge to the test agents, to reflect the severe problems that these systemic mycoses often present in seriously ill individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The relative failure of oral agents like itraconazole and fluconazole was somewhat surprising, because they have been reported to be effective in the therapy of experimental fungal infections in mice (5,11,25). In the current study, the model infections were designed to present a formidable challenge to the test agents, to reflect the severe problems that these systemic mycoses often present in seriously ill individuals.…”
Section: Resultsmentioning
confidence: 99%
“…In the study described here we examined the utility of D0870 as a therapy for experimental systemic histoplasmosis in immunocompetent mice. Fluconazole was chosen as the comparison drug on the basis of the results of clinical trials that demonstrated the clinical improvement of immunocompetent patients with histoplasmosis treated with fluconazole (3), in addition to the efficacy of fluconazole shown in animal models of histoplasmosis (6,10,11).…”
mentioning
confidence: 99%
“…The antimicrobial treatment period for such infection models may be longer than the routine PD50 experiments, since many infections in immunosuppressed patients are chronic in nature and require treatment over a period of time longer than 48 h. Chronic protection studies of this type often require different criteria for measuring successful therapy compared with routine PD50 studies that usually record lethality. These criteria can include counting viable microbial cells in one or more infected organs of animals sacrificed during, or at the completion of, a course of therapy (91). Measurement of microbial cell clearance from infected tissues is another way of assessing how well a test antibiotic might work in many of the serious infections encountered in humans.…”
Section: Animal Models For Studying the Pharmacokinetics Andmentioning
confidence: 99%
“…Furthermore, with the increased incidence of immunosuppressed patients seen in hospitals today, there is a major need for new antimicrobial agents that provide adequate therapy in patients lacking an intact immune system (57,98,134). Therefore, new infection models have been developed in immunosuppressed animals that measure the efficacy of antimicrobial agents against bacterial and fungal pathogens found in immunosuppressed patients (6,91,132). Usually, the animals are chemically immunosuppressed with repeated doses of agents such as dexamethasone or cyclophosphamide before challenge with a lethal inoculum of test organism (91,132).…”
Section: Animal Models For Studying the Pharmacokinetics Andmentioning
confidence: 99%
See 1 more Smart Citation